PERBEDAAN FEAR OF COMPASSION PADA MAHASISWA DI PROGRAM STUDI PSIKOLOGI UNIVERSITAS NEGERI MANADO - Veren D. P. Mondigir; Meike E. Hartati; Marssel M. Sengkey (Program Studi Psikologi Universitas Negeri Manado, 2022)
This study aims to determine the differences in fear of compassion among students in class 2019 and class 2021 at the Psychology Study Program, Manado State University. This research method uses quantitative research methods. The subjects of this study used 187 students in the Psychology Study Program at Manado State University using a purposive sampling technique. This research instrument modifies the fear of compassion scale from Paul Gilbert et al (2011) with 46 items. The research was tested using the Independent Sample T Test. Based on the results of the study, it shows that there is a difference in fear of compassion in the 2019 and 2021 classes.